ANALISIS PROSEDUR RESTITUSI KELEBIHAN PEMBAYARAN PAJAK PERTAMBAHAN NILAI PADA KANTOR PELAYANAN PAJAK PRATAMA PEMATANG SIANTAR - Lingga, Felik Jianli Princen; Saragih, Afni Eliana (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to determine how the implementation of restitution procedures at KPP Pratama Pematang Siantar. The population of this research is the entire procedure of VAT refunds for corporate taxpayers at KPP Pratama Pematang Siantar. The sample of this research is the procedure of VAT refunds for 2017-2021 corporate taxpayers recorded at the KPP Pratama Pematang Siantar. The analytical method used is descriptive analysis by collecting restitution procedures. Based on the results of the study, it shows that the application of the restitution procedure at the Pematang Siantar KPP Pratama has not been realized properly, there are still many taxpayers who do not complete the documents requested by the Pematang Siantar KPP Pratama and the application of the restitution procedure that occurs at the Pematang Siantar KPP Pratama is not in accordance with the restitution procedure in accordance with the provisions Applicable laws and SOP. Keywords: Value Added Tax, Tax Overpayment, Restitution, Restitution Procedure